Cloning, Expression, Purification, and Oligomeric Characterization of the AopB-C-terminus Domain in T3SS Major Translocator Protein of Aeromonas hydrophila - Van Sang, Nguyen; Uyen, Nguyen Thi (VNU Journal of Science: Natural Sciences and Technology, 2021)
Type three secretion system (T3SS) is found exclusively in gram-negative pathogens such as Yersinia spp ., Escherichia coli , Salmonella spp ., Shigella spp ., Pseudomonas spp ., Vibrio parahaemolyticus , and Aeromonas hydrophila . The translocon pore of T3SS comprises major and minor translocator proteins that assemble to provide passage of effectors through the host cell membrane. Major translocator protein AopB from Aeromonas hydrophila plays an important role in translocon pore formation. Despite tremendous efforts, structural information regarding the C-terminus domain of major translocator AopB remains elusive. In this study, the DNA fragment encoding for the C-terminus domain of the AopB major translocator from Aeromonas hydrophila AH-1 was cloned in to pET-M expression vector and expressed in BL21 (DE3) host cells. The recombinant AopB-C-terminus domain was successfully purified using immobilized nickel affinity chromatography as a soluble form. Crosslinking analysis among AopB-C-terminus molecules in solution showed that this domain exists as a mixture of tetramer, trimer, dimer and monomer forms. The three-dimensional structure model of AopB-C-terminus oligomerization was built by SWISS-MODEL and PyMol. The oligomeric model of AopB-C-terminus can be used for structural studies of the AopB-C-terminus domain which can contribute to the elucidation of the structure of the type III secretion system.